GOLKAR DALAM MENAPAK PEMILIHAN UMUMORDE BARU Golkar in The New Order General Election - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT The superior of Golkar in every general election, which has placed it to be a hegemony party, is not fully its efforts, but because of military and bureaucracy capabilities and efforts to mobilize mass votes for meeting Golkar's interest. Other supporting factors were government policy which tended to benefit Golkar, such as No. 12, 1970 of Ministry Ultimatum, Floating mass policy, Party fusion policy, and single principal ideology as operational basis by political parties and mass organizations. In other words, general election has been manipulated in order to make Golkar always be a superior. The Golkar's victory has not always showed the increasing trends. In 1992 general election, for example, the number of Golkar's vote was slightly declined, but this did not change its position as a single majority. From this condition, however, it can be learned that when the principle of democracy process was being applied, there would be tendencies that political interest of society would be articulated to others. This conditions have been proved by some factors, such as, some conducive conditions created before general election accomplished particularly before 1992's general election